2001
DOI: 10.1073/pnas.131195198
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 but not omega 6 fatty acids inhibit AP-1 activity and cell transformation in JB6 cells

Abstract: Epidemiological and animal-based investigations have indicated that the development of skin cancer is in part associated with poor dietary practices. Lipid content and subsequently the derived fatty acid composition of the diet are believed to play a major role in the development of tumorigenesis. Omega 3 (3) fatty acids, including docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), can effectively reduce the risk of skin cancer whereas omega 6 (6) fatty acids such as arachidonic acid (AA) reportedly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 48 publications
5
56
1
1
Order By: Relevance
“…In this regard, Liu et al, (2001) showed that in a mouse epidermal cell system, w3-PUFAs, but not the w6-arachidonic acid, effectively inhibited growth factor-triggered activator protein-1 transactivation. Moreover, w3-PUFAs down-regulated cytokine-triggered NF-kB activation and subsequent gene transcription in endothelial cells (McGuinness et al, 2008) as well as in macrophages (Lo et al, 1999).…”
Section: Figurementioning
confidence: 99%
“…In this regard, Liu et al, (2001) showed that in a mouse epidermal cell system, w3-PUFAs, but not the w6-arachidonic acid, effectively inhibited growth factor-triggered activator protein-1 transactivation. Moreover, w3-PUFAs down-regulated cytokine-triggered NF-kB activation and subsequent gene transcription in endothelial cells (McGuinness et al, 2008) as well as in macrophages (Lo et al, 1999).…”
Section: Figurementioning
confidence: 99%
“…Furthermore, asphalt fumes promote cell transformation. Up-regulation of AP-1 activity is frequently associated with cell transformation, and blockage of AP-1 activity has been shown to reverse the transformation of mouse epidermal cells (10,13,17,18,40). Many intracellular signaling pathways either directly or indirectly regulate AP-1 activation and cell transformation.…”
Section: Fig 4 Effect Of Asphalt Fumes On Pi3k Activity In Jb6 Pmentioning
confidence: 99%
“…Transformation-Increased AP-1 activity leads to malignant transformation, and thus, the suppression of AP-1 activity is suggested to be involved in the mechanisms of action of many potential chemopreventive agents (25)(26)(27). We therefore investigated whether NS-398 or piroxicam could block malignant cell transformation.…”
Section: Ns-398 or Piroxicam Inhibits Tpa-induced Ap-1 Activity And Cellmentioning
confidence: 99%